Challenging prevailing narratives with Twitter: An #AustraliaDay case study of participation, representation and elimination of voice in an archive. (September 2018) - Fransen-Taylor, Pamela; Narayan, Bhuva
Social media, specifically a microblogging service such as Twitter, constitute a public space that has changed how we interact with, exchange, and respond to information in a civil society. They also have the potential to give public voice to minority narratives that are under-represented in the mainstream media, just as grassroots graffiti in public spaces have done over human history. Using a specific case study around an issue in the Australian national discourse around Australia Day, this study contributes new insights towards an understanding of how alternate narratives are expressed and erased in cyberspace, just as graffiti are erased from public view by the authorities. Widely promoted by official sources as a day of festivity and celebration, the Australia Day Your Way initiative actively promotes the use of the hashtag #AustraliaDay to metatag tweets for capture to an annual time capsule stored by the National Museum of Australia. For Australia's indigenous minority though, Australia Day is symbolic of an entirely different narrative, expressed online through the hashtags #InvasionDay and #SurvivalDay. We studied all three hashtags and their intersections on Twitter and also compared this data to what was showcased in the official time capsule. We found that although the alternative voices existed on Twitter, they were excluded from the official time capsule. This has implications both for archives and for future historians studying contemporary events.